2011
DOI: 10.1016/j.psychsport.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Extra-curricular sport participation: A potential buffer against social anxiety symptoms in primary school children

Abstract: The present research: Proposal for the design of a sports school for soccer and volleyball for children and young people aged 6 to 14 years with a focus on constructivism, carried out between 2019 and 2020, aims to propose the design of a soccer and volleyball sports school related to a constructivist model, as a strategy for the free use of children and young people aged 6 to 14 years of the Caldas Institute. The methodology developed was based on a quantitative approach, non-experimental and descriptive desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 37 publications
9
41
1
3
Order By: Relevance
“…A recent study [37] incorporated Antonovsky’s Salutogenesis model [67] and Bandura’s theory of Social Learning [68]. The foundation of Antonovsky’s model is that heterostasis, ageing and progressive entropy are core characteristics of all living organisms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study [37] incorporated Antonovsky’s Salutogenesis model [67] and Bandura’s theory of Social Learning [68]. The foundation of Antonovsky’s model is that heterostasis, ageing and progressive entropy are core characteristics of all living organisms.…”
Section: Resultsmentioning
confidence: 99%
“…The model focuses on what makes a person maintain good health rather than focusing on the aetiology of sickness. In terms of the Social Learning theory, it is suggested that organised sport, particularly in teams, could be an important factor in a child’s social development [37]. However, this was a general discussion comment, and it is not clear how the Social Learning Theory was applied in the methodology of this study [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, longitudinal findings remain limited and mixed. For example, some studies suggest no benefits of sport frequency,14 no benefits team versus individual sport,24 or reductions in social anxiety in response to individual sport compared with team sport 15…”
Section: Introductionmentioning
confidence: 99%
“…La influencia del proceso de socialización y relación con los pares en las actividades deportivas hace que cobre una especial importancia al estudio del efecto de los deportes de equipo frente a deportes individuales, encontrándose mayores beneficios cuando se practica deporte de equipo, por ejemplo, en el decremento de la ansiedad social (Schumacher y Seiler, 2011).…”
Section: Introductionunclassified